Indonesia’s Defense Diplomacy Toward Fiji on the Papua Issue: Strengthening Bilateral Cooperation and Regional Stability - Estirahayu, Ferditania; Perwita, Anak Agung Banyu; Hendarwoto, Yermia (International Journal of Humanities, Education, and Social Sciences, 2025)
This study analyzes Indonesia’s defence diplomacy towards Fiji through the combined lenses of neorealism and soft power to explain Jakarta’s strategic conduct in the South Pacific. In a regional environment where states prioritize security and survival, Indonesia’s engagement with Fiji represents a calculated, non-coercive approach to advancing national interests, particularly regarding the Papua issue. Defence diplomacy initiatives include officer training programmes, high-level visits, joint military exercises, and institutionalised strategic dialogues designed to promote trust, transparency, and mutual understanding. Empirical evidence highlights the participation of Fijian officers in Indonesia’s Army Staff and Command College and Peacekeeping Centre, as well as bilateral commitments to expand cooperation across the army, navy, and air force. These activities have coincided with a moderation of Fiji’s stance on Papua in regional forums, aligning more closely with Indonesia’s position. Humanitarian assistance, capacity-building measures, and regional security collaboration have further enhanced Indonesia’s diplomatic image and supported its free and active foreign policy. The study concludes that Indonesia’s defence diplomacy towards Fiji serves both as a structural security strategy and a normative engagement tool, generating mutual benefits while strengthening Jakarta’s strategic influence in the Pacific.